The Cross-Cultural Specificity of The Taboo Is the Example of The English and Uzbek Languages (Eurasian Journal of Learning and Academic Teaching, 2023)
This article discusses the definitions given by researchers to the word taboo, as well as the uniqueness of taboos in English and Uzbek culture. The similarities and differences between the taboos of both cultures are discussed. In addition to that, this article provides information about the words used instead of taboos